ENHANCED HETEROLOGOUS EXPRESSION IN E.COLI - NAGY, Katalin; KOVÁCS, Zita; SALAMON, Pál; ORBÁN, Csongor-Kálmán; LÁNYI, Szabolcs; ALBERT, Beáta (Studia Universitatis Babeș-Bolyai Chemia, 2019)
Apoptotic regulation has been implicated in many human diseases, including cancer, autoimmune disease, inflammation and neuro degradation. Mapping up critical apoptosis regulators is a strategy for the development of new therapies [1, 2]. Present work highlights optimization of heterologous expression conditions for the X-linked inhibitor of apoptosis protein (XIAP). Genes of target protein containing pGEX-4T vector was transformed in chemically competent E. coli Rosetta™(DE3)pLysS cells. The recombinant construct contained a glutathione S-transferase (GST) fusion partner, which assured the purification of the protein by affinity chromatography. In the next step, we examined the growth dynamics of the expression culture in M9 minimal medium, meanwhile we also determined the appropriate time of induction. Following this we carried out the optimization of expression, examining the expression’s effectiveness under different conditions. On the basis of these fermentation experiments the target protein expression was the most prominent at 18 °C with 0.2 mM IPTG induction for 12 hours. During large scale fermentation experiments, we followed the optical density (OD), dry cell weight and substrate utilization. Finally, recombinant protein expression inhancement in the presence of 3% ethanol was successfully achieved in bioreactor. In this case, the target protein was expressed in inclusion bodies, therefore solubilisation and refolding is necessary.